2022
DOI: 10.1371/journal.pone.0260840
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antenatal exercise in Arba Minch town, Southern Ethiopia: A community-based cross-sectional study

Abstract: Background Many health risks in pregnant women and their foetuses can be reduced by practicing antenatal exercise. However, the adequate practice of antenatal exercise among pregnant women is low in Ethiopia. Therefore, this study aimed to assess the practice of antenatal exercise and its associated factors among pregnant women in Arba Minch town. Methods A community-based cross-sectional study design was conducted. Data were collected by using a structured questionnaire from 422 pregnant women selected by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…We used a multivariable logistic regression model to identify factors associated with physical inactivity during pregnancy in Shanghai and found that women who had engaged in regular exercise before pregnancy were more likely to have a higher PA level during pregnancy than women who had not, which is consistent with studies from Arba Minch Town in Ethiopia [19], Campinas in Brazil [18], data from the US Centers for Disease Control and Prevention [14] and a study performed in Chengdu in China [15]. This nding indicates that starting exercise before conception may help women to achieve adequate PA during pregnancy and underscores the importance of lifestyle changes before pregnancy.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…We used a multivariable logistic regression model to identify factors associated with physical inactivity during pregnancy in Shanghai and found that women who had engaged in regular exercise before pregnancy were more likely to have a higher PA level during pregnancy than women who had not, which is consistent with studies from Arba Minch Town in Ethiopia [19], Campinas in Brazil [18], data from the US Centers for Disease Control and Prevention [14] and a study performed in Chengdu in China [15]. This nding indicates that starting exercise before conception may help women to achieve adequate PA during pregnancy and underscores the importance of lifestyle changes before pregnancy.…”
Section: Discussionsupporting
confidence: 72%
“…First, we used backward elimination to remove variables with a p-value >0.2. Second, considering maternal age, level of education, pre-pregnancy BMI, parity, and history of spontaneous abortions to be clinically relevant or related to the level of PA in previous studies [19,20,23], we also added these ve variables into the model. Finally, maternal age, level of education, current employment status, personal monthly income, pre-pregnancy BMI, regular exercise before pregnancy, alcohol consumption before pregnancy, history of spontaneous abortions, parity, stage of pregnancy, nausea and vomiting during pregnancy, and prenatal sleep quality were entered as independent variables into the logistic regression model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies are three in Tigray region [ 21 , 25 , 34 ], while Amhara region [ 18 , 23 ], SNNPR (Southern Nations Nationalities and People’s Region) region [ 20 , 24 ] and Addis Ababa city contributed two studies each [ 35 , 36 ], and Harar [ 37 ] and Sidama regions represented by one study each [ 19 ]. All of the included articles were cross-sectional studies [ 18 21 , 23 25 , 34 – 37 ], and the included sample ranges from 240 to 806 pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…In one paper, there was a suggestion that PA intensity could be increased by encouraging more PA before pregnancy ( 40 ). Low education ( 32 , 35 , 36 , 43 , 46 , 54 ), first parity ( 29 , 36 , 43 ), lack of knowledge and skills ( 27 , 33 , 44–46 , 53 , 55 ), pregnancy symptoms ( 25 , 27 , 28 , 32 , 33 , 35 , 43 , 44 , 51–53 , 55 ), lack of time ( 25 , 27 , 33 , 39 , 44 , 53 ), low income ( 27 , 33 , 39 , 45 , 51 , 53 ), lack of motivation/goal ( 25 , 51 , 53 , 55 ), and safety concerns ( 25 , 27 , 29 , 31 , 33 , 34 , 44–46 , 49 , 51 , 53 , 55 ) were all identified by the researchers as barriers. The lack of time mainly came from family commitments ( 44 ), while low education, first parity, and lack of knowledge and skills were all related to safety concerns.…”
Section: Discussionmentioning
confidence: 99%